The common fatty acids of human depot fat - Krut, Louis Harold (Department of Medicine, 2020)
The current renaissance in biological research has evoked widespread interest in the field of lipid metabolism. While extensive studies during the past decade have greatly expanded our knowledge of the subject, these researches have been directed primarily to the serum lipids. By far the greatest accumulation of lipid in the mammalian organism is found in the depot fat. This tissue had, until fairly recently, been generally regarded as a semi-static food store, expanding and shrinking in response to a relative excess or deficit of dietary calories. This simple concept is no longer tenable. The pioneering work of a few workers in the field during the past few decades has more recently interested many others and the accumulated evidence has established the fat depot among the more active organs in the mamnalian organism.